Acesso à justiça a partir da análise do ambiente virtual brasileiro: uma perspectiva interdisciplinar CTS - Nascimento Junior, Vanderlei de Freitas (2023)
Based on innumerable scientific advances witnessed by mankind in the last decades, especially after the creation of computers and the Internet itself, it is a fact that the area of social communication has significantly changed the lives of humans and other living beings. The barriers of time and space have been broken down, and virtual interactions between different types of people, whether individuals or companies, have intensified even more. Old habits of the Brazilian democratic society have been changed. But how to guarantee the good use of the internet by its respective users? What is the reality of the Brazilian virtual environment? Questions like this are capable and necessary to make human beings look at themselves and re-signify their own lives, as inhabitants and members of an international community. New conflicts have arisen, new forms of social interaction have been created or consolidated, and new forms of exclusion have emerged in today’s society. Facing this new social reality, both the law and other scientific areas related to applied social sciences have felt the need for an interdisciplinary re-reading of the Access to Justice principle, in order to bring it closer to the idea of Political Justice. In this sense, it should be clarified that the objective of this work is to analyze social interactions and the means of guaranteeing Justice (Politics) in the Brazilian virtual environment, from the interdisciplinary perspective of the field of Science, Technology and Society (STS). Some theoretical mentions were made on Scientific Interdisciplinarity, Democracy, Citizenship, Access to Justice and Virtualization of Social Interactions. Such topics were analyzed under the viewpoint and interdisciplinary perspective of the Science, Technology and Society (STS) field, thus allowing the observation of the intersection between several sciences, such as Law, Sociology, Social Communication, Political Sciences, Philosophy and Education. It is believed that only from a broad view about the real meaning of Justice, the humanity will man be able to self-determine and ensure his preservation in a society which increasingly becomes virtually integrated. For this purpose, descriptive exploratory methodological techniques were used, based on historical, bibliographical and normative analysis, due to the essentially qualitative nature of this thesis. In addition, an attempt was made to demonstrate through deductive and dialogic methods that the assumptions brought as theoretical references, when analyzed under the STS perspective, began to dialogue with each other, aiming to answer the following questions: i) How can the principle of Access to Justice be reinterpreted, considering the main characteristics of contemporary Brazilian society, especially in relation to the growing interactions in the virtual territory? ii) What contribution can the field of Science, Technology and Society make to carry out this reinterpretation? It is intended, therefore, to reach the conclusion that the best interpretation that can be given to the term Justice is the one that refers to the meaning of Political Justice.